Erosion-induced carbon losses and CO2 emissions from Loess and Black soil in China - Gao, Xin; Hu, Yaxian; Sun, Qiqi; Du, Lanlan; Duan, Pengfei; Yao, Lunguang; Guo, Shengli (Catena (Giessen), 2018)
Soil erosion influences both lateral soil organic carbon (SOC) re-distribution and vertical soil CO2 emissions. While potential SOC mineralization during transport and the burial effects of SOC at depositional sites have been addressed in previous reports, erosion induced on-site CO2 emissions are still under-studied. In this study, two soils (Loess soil and Black soil) with similar texture but contrasting aggregate structure and SOC content were subject to a set of 60-min long simulated rainfall events. There were two different rainfall intensities (30 and 90 mm h−1) at three slope gradients (5°, 15° and 25°). Runoff and sediment from erosion plot were collected at 10-min intervals over 60 min. Soil CO2 emissions from eroding slopes, SOC and particle size distribution of the eroding soil were measured after the erosion events. The results show that the runoff rates from the two soils were comparable, but the sediment rates from the Loess soil roughly three times that from the Black soil. In general, the SOC erosion from the Loess soil was 1.8 times that from the Black soil, even though the SOC concentration in the original Black soil was 56% higher than the Loess soil. The cumulative soil CO2 emissions from the eroding slopes of the Loess soil ranged from 15.4 to 19.7 g C m−2, which was doubled on the Black soil (from 28.1 to 59.6 g C m−2). When the rainfall intensity raised from 30 mm h−1 to 90 mm h−1, the cumulative soil CO2 emissions from the Black soil decreased by 38.2%, but only declined by 10.0% on the Loess soil. When the slope gradient increased from 5° to 25°, the cumulative soil CO2 emissions decreased by 23.8% on the Black soil but by 12.6% on the Loess soil. Therefore, our observations suggest that the soil CO2 emissions on the Black soil was much more sensitive to the variations of rainfall intensity and slope gradients than the Loess soil. Greater SOC erosion should not be directly translated to less on-site soil CO2 emissions. The selective depletion/enrichment of SOC and the lability of individual components must be fully understood when accounting for slope-scale carbon balances. •Loess soil has lower SOC content but greater SOC erosion than Black soil.•On-site soil CO2 emissions on Black soil decreased with erosion intensity.•On-site soil CO2 emissions on Loess soil barely changed with erosion intensity.•Greater SOC erosion does not mean less on-site soil CO2 emissions.•On-site CO2 emissions from Black soil may not be regulated by erosional removal but by inherent SOC.